Towards an Ontology of Information and Succeeding Fundamentals in Computing Science - Gerhard Luhn (tripleC: Communication, Capitalism & Critique)
A common usage of the concept of information requires a unique definition of it. The text expands on a proposal for an ontology of information, which will be grounded in physics. Shannon’s communication theory does not conceptualize any physical variable. It will be shown that by doing so the gap between syntax and semantics can be closed by introducing the universal category of triadic information. Any informational scenario is given by the trias of a) a sender, and of b) the transformation, which happens to c) the receiver. The concept of information is taken in a broader sense, and is based on physical fundaments. The gravitational force which is exploited to a physical body holds in the same sense well defined information as a spontaneous appearance of a new, algorithmically underivable structure or event: the world gets ‘com- pleted’ within a continuous informational process. Any spontaneous process will always happen in order to increase the entropy of the world. That is, such fundamental information, which causes this completion process, is given within our uni- verse. For those reasons we have to state, that information causes any causal process, rather than ‘is’ a causal process. All living species are grounded on an information-receiving, heteronomous deep structure, which includes as well the message which corresponds to further autonomy and freedom (the completion theorem). To summarize, we are enabled to create and to enter into the so called information society by ontological evidence. Based on such foundations, an adequate concept for computer science will be shortly introduced.